2010
DOI: 10.1177/0269216310376119
|View full text |Cite
|
Sign up to set email alerts
|

Pressure ulcers in cancer palliative care patients

Abstract: Terminally ill cancer patients are considered at high risk for pressure ulcers because of their clinical condition. However, in Italy, data about pressure ulcers and their prevalence are insufficient. This paper reports a study on pressure ulcers incidence and prevalence in a population of oncology patients cared for in an Italian palliative care service. A retrospective analysis of 414 clinical records of patients admitted over 6 months showed a prevalence of pressure ulcers of 22.9% and an incidence of 6.7%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 12 publications
5
44
1
6
Order By: Relevance
“…The characteristics of PU are shown in table 3. in palliative care (6)(7)(8)(12)(13)(14)(15)(16) . In studies carried out in other countries, the prevalence of PU in people in palliative care (PC) ranged from 10.5 to 26% (6)(7)(8)12) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of PU are shown in table 3. in palliative care (6)(7)(8)(12)(13)(14)(15)(16) . In studies carried out in other countries, the prevalence of PU in people in palliative care (PC) ranged from 10.5 to 26% (6)(7)(8)12) .…”
Section: Resultsmentioning
confidence: 99%
“…In studies carried out in other countries, the prevalence of PU in people in palliative care (PC) ranged from 10.5 to 26% (6)(7)(8)12) . In Canada, a study with people with advanced cancer from a home care agency identified a prevalence of PU of 10.5% (7) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A diferença de cuidados necessários para cada gênero pode ser percebida, por exemplo, nas manobras e nos posicionamentos mais difíceis nos homens, além da menor disposição deles em admitir a necessidade de recorrer a cuidados formais adicionais (HENDRICHOVA et al, 2010).…”
Section: Discussionunclassified